Redesign a part of the city. From polluting road to sustainable linear square in three “P”: profile, permeability, photocatalysis. - Alessandro Luigini (Vitruvio: International Journal of Architectural Technology and Sustainability)
The project presented here is a best practice applied to the routine of public service work. The financial investment necessary to ground makeover asphalt was diverted for a functional and environmental regeneration of an area of almost one hectare. The project, basically, wonders about the many possibilities of urban renewal that can arise from the ordinary activities of public works management, and how targeted action can bring parts of cities to a more appropriate relationship with the environment.